Effectiveness of using Driver's model in developing mathematical concepts among primary school students in Al-Kharj Governorate - Al-Harthy, Wafaa Ayed; Saedan, Sheikha Muhammad (Journal of Curriculum and Teaching Methodology, 2022)
The study aimed to reveal the effectiveness of using Driver's model in developing mathematical concepts among primary school students in Al-Kharj Governorate. The study relied on the quasi-experimental approach, and the study sample consisted of (37) female students from the fourth grade of primary school in the fourteenth primary school in Dulm for the second semester of the academic year 1442/1443 AH, where they were randomly selected and distributed into two groups, the control group consisted of (18) A female student, who studied the development of mathematical concepts for geometric shapes and spatial inference from the mathematics book for the fourth grade of primary school in the usual way, and the experimental group consisting of (19) students, studied the same subject using the Driver model, and the tools consisted of the development of mathematical concepts test, and the teacher’s guide. The results indicated that there was a statistically significant difference between the students of the control and experimental groups of the fourth grade students on the post-test development of mathematical concepts in favor of the experimental group that studied using the Driver model, and the presence of statistically significant differences between the mean scores of the experimental group students on the mathematical concepts development scale in The pre and post application on the effectiveness of Driver's model in the mathematical concepts of geometric shapes and spatial inference for the benefit of the post application. The study recommended the necessity of employing Driver's model in developing concepts in mathematics and other sciences, and holding training courses for teachers to apply Driver's model in developing concepts and correcting alternative perceptions among students.
Keywords: Driver's model; mathematical concepts; effectiveness; the primary stage